Designing Behavioral Mental Health Rehabilitation Center in Medan - Tiffany Marchel Lie; Dwira Nirfalini Aulia (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The advancement of technology and changes in lifestyle have become triggers for deviant behavior, potentially causing mental health issues. Mental health is an increasingly crucial aspect of societal well-being. Optimal mental health impacts individuals' awareness of their potential, their ability to manage life pressures stably, productive performance in work, and active participation in community life. The negative stigma in society towards individuals with mental disorders further exacerbates the number of affected individuals. In Indonesia, this issue is gaining more attention due to its impact on the quality of life for individuals and society as a whole. Mental disorders necessitate a holistic and innovative approach to rehabilitation efforts. Therefore, it is essential to establish specialized rehabilitation centers for individuals with mental disorders, providing support in both physical and mental recovery processes. Well-designed and functional spaces play a key role in enhancing the psychological well-being of individuals, creating an environment that is safe, comfortable, and preserves privacy. By adopting the Behavioral Architecture approach in design, it is expected to create an environment that meets the needs of patients and positively influences the behavior, perceptions, and feelings of everyone involved in the activities.